Investigating the effectiveness of brief cognitive reappraisal training to reduce fear in adolescents - Shore, T; Cohen Kadosh, K; Lommen, M; Cooper, M; Lau, J (Taylor and Francis, 2019)
As adolescent anxiety is common and costly, identifying effective strategies to reduce symptoms is a priority. This study tested whether adolescents could learn to use cognitive reappraisal strategies to attenuate fear during extinction learning. Fifty-seven participants (12–15 years) viewed images of two neutral faces, one which was paired with a fearful expression and shrieking scream (conditioned threat stimulus) and the other that was never paired with the aversive outcome (conditioned safety stimulus) during fear acquisition. Before extinction, participants either received cognitive appraisal training, which explored alternative, benign meanings associated with the scream or a control activity. Self-reported fear ratings in the cognitive reappraisal group were significantly lower to both the conditioned threat and safety stimuli after extinction than the control group. These findings did not characterise fear-potentiated startle data. Potential reasons for the lack of consistency between measures are considered.